Navigating English Language for Specific Needs: Schools Stakeholder in Overcoming International School - Manggiasih, Laras; Wahyuni, Sri; Loreana, Yurike Risa; Nurjati, Nunung (IJET (Indonesian Journal of English Teaching), 2023)
This study aimed to investigate the challenges encountered by English for Specific Purposes (ESP) learners in their journey to enhance English language proficiency. A mixed-methods approach was adopted, incorporating a comprehensive literature review and conducting semi-structured interviews with three ESP teachers and three administrative staff members from the same educational institutions. The findings from the literature review revealed that ESP learners often struggle with managing their time effectively due to the demands of their personal commitments, learners' self-efficacy in facing confidence issues, fear of making mistakes, and negative past experiences hindering their language learning progress. Moreover, limited access to authentic materials tailored to their specific fields emerged as a crucial obstacle, impacting learners' ability to develop subject-specific vocabulary and comprehend real-world language use. By recognizing and addressing these challenges, educators and institutions can develop more targeted and effective language learning strategies, ultimately empowering ESP learners to overcome their obstacles and achieve higher levels of English proficiency